2009
DOI: 10.1002/ejoc.200801183
|View full text |Cite
|
Sign up to set email alerts
|

Development of Analogues of 1α,25‐Dihydroxyvitamin D3 with Biased Side‐Chain Orientation: C20 Methylated Des‐C,D‐homo Analogues

Abstract: The discovery that 1α,25-dihydroxyvitamin D 3 is effective in the inhibition of cellular proliferation and in the induction of cellular differentiation has led to a search for analogues in which these activities and the classical calcemic activity of the hormone are dissociated. In this context, the synthesis and biological evaluation are reported for six CD-ring modified structural analogues that were conceived so as to enforce a particular orientation of the 25-hydroxylated side chain. The analogues are char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…16 This synthesis has been used to access the natural hormone 1,25D 17 and a variety of vitamin D analogues modified at the side chain, 13 triene system, 18 C-ring, 19 and Aring, 11,20 that were required to establish structure−function relationships for the development of active ligands of the VDR with potential therapeutic value. Biological studies on analogues with modified C/D region that comprise C-ring analogues lacking the D-ring, 21,22 D-ring analogues lacking the C-ring 23,24 and six-membered D-ring analogues, 25,26 have demonstrated that the native bicyclic CD-core is not required for biological activity and its alteration might lower the calcemic activity. 27 In a search for vitamin D analogues that are highly active in the circulation but with low or negligible calcemic effects, we describe a modification of the reported synthetic approach for rapid and economic access to novel vitamin D analogues 2 (Figure 1a) and disclose their structures and their biological activities with respect to cell differentiation-proliferation, transactivation, and secondary calcemic effects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16 This synthesis has been used to access the natural hormone 1,25D 17 and a variety of vitamin D analogues modified at the side chain, 13 triene system, 18 C-ring, 19 and Aring, 11,20 that were required to establish structure−function relationships for the development of active ligands of the VDR with potential therapeutic value. Biological studies on analogues with modified C/D region that comprise C-ring analogues lacking the D-ring, 21,22 D-ring analogues lacking the C-ring 23,24 and six-membered D-ring analogues, 25,26 have demonstrated that the native bicyclic CD-core is not required for biological activity and its alteration might lower the calcemic activity. 27 In a search for vitamin D analogues that are highly active in the circulation but with low or negligible calcemic effects, we describe a modification of the reported synthetic approach for rapid and economic access to novel vitamin D analogues 2 (Figure 1a) and disclose their structures and their biological activities with respect to cell differentiation-proliferation, transactivation, and secondary calcemic effects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The replacement of the five-membered D-ring of analog SL 117 by a six-membered ring (BL 269) resulted in a more potent analog (three-fold increased inhibition of MCF-7 or keratinocytes proliferation compared to 1,25(OH) 2 D 3 ) (Table 76.9) [34,35]. The introduction of other modifications (20-epi; 16-ene-23-yne) did not enhance the potency of BL 269.…”
Section: D-ring Analogsmentioning
confidence: 99%
“…Over the years numerous analogs were developed featuring a more substantially modified CD-region such as the six-membered C-ring analogs (lacking the D-ring, Tables 76.3e76.4) [30,31], five-membered D-ring analogs (lacking the C-ring, Tables 76.5e76.8) [32,33] and six-membered D-ring analogs (lacking the C-ring and possessing an enlarged D-ring, Table 76.9) [34,35]. In comparison with the natural compound 1,25(OH) 2 D 3 , the non-steroidal analogs described in this section possess a greater flexibility.…”
Section: C-and D-ring Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Therefore, Peterson olefination was chosen to inhibit undesired epimerization. Happily, the Peterson olefination (LDA, TMSCH 2 CO 2 Et) 10 of 10 gave desired enoate 11 in 91% yield as a mixture of Z / E isomers (1.25:1). Subsequent copper hydride reduction 11 was sluggish when using PhSiH 3 as reductant.…”
Section: Table 1 Antiproliferative Activity Of (+)-King...mentioning
confidence: 99%